2022
DOI: 10.3390/cancers14122984
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Fibrosis at Diagnosis and during the Course of Disease Is Associated with TP53 Mutations and Adverse Prognosis in Primary Myelodysplastic Syndrome

Abstract: The prognostic significance of bone marrow fibrosis (MF) grade in patients with myelodysplastic syndrome (MDS) is still debated and the molecular changes remain unclear. In our large cohort, a normal reticulum was found in 211 (25.9%) patients, whereas MF1, MF2 and MF3 were detected in 478 (58.7%), 90 (11.1%) and 35 (4.3%) patients at initial diagnosis, respectively. Patients with MF often correlated with some poor prognostic characteristics, including older age, anemia, unfavorable karyotype, higher BM blast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…BMF in MDS is associated with deep cytopenias and increased need for red blood cell and platelet transfusion. 10,17,18 The depth of cytopenia and the need for transfusion remain as an important prognostic variable used in MDS patients, included in the International prognostic scoring system (IPSS) and the World Health Organization Prognostic Scoring System (WPSS). In a study of 301 patients with MDS, shorter overall survival and leukemia-free survival were found in patients with grade 2 and 3 BMF, and this effect was interpreted as an independent marker of increased blastic cell population in the bone marrow.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BMF in MDS is associated with deep cytopenias and increased need for red blood cell and platelet transfusion. 10,17,18 The depth of cytopenia and the need for transfusion remain as an important prognostic variable used in MDS patients, included in the International prognostic scoring system (IPSS) and the World Health Organization Prognostic Scoring System (WPSS). In a study of 301 patients with MDS, shorter overall survival and leukemia-free survival were found in patients with grade 2 and 3 BMF, and this effect was interpreted as an independent marker of increased blastic cell population in the bone marrow.…”
Section: Resultsmentioning
confidence: 99%
“…Another disease in which bone marrow fibrosis is most frequently detected is MDS. BMF in MDS is associated with deep cytopenias and increased need for red blood cell and platelet transfusion 10,17,18 . The depth of cytopenia and the need for transfusion remain as an important prognostic variable used in MDS patients, included in the International prognostic scoring system (IPSS) and the World Health Organization Prognostic Scoring System (WPSS).…”
Section: Discussionmentioning
confidence: 99%
“…Although more frequent in MPN, progressive MF occurs in MDS too, more often in occasions, which initially present with JAK2 V617F mutation. This is a very rare finding in MDS, associated with poor outcome that is independent of transformation to sAML [65]. In addition, MF progression is linked to the acquisition of JAK2 and SRSF2 mutations and increased gene expression of MMP2 , MMP14 , SMAD3 , SMAD4 , TGFB1 , THBS1 , TIMP1 , and miR-146b, as well as increased CD42b + pro-platelet deposition in the BM [66].…”
Section: Progressive Mfmentioning
confidence: 99%
“…Hence, the nomenclature MDS-f applies only to fibrotic marrow (grade 2 or 3 on a 3-grade scoring system, based on reticulin and trichrome stains) with either 5% to 19% blasts in the bone marrow or 2% to 19% blasts in peripheral blood. Cumulative evidence has shown that MDS-f at the time of initial diagnosis is an independent factor associated with overall worse survival in patients treated with traditional hypomethylating agents 32,33 ; although fibrosis in MDS is associated with TP53 mutations, a multihit TP53 mutation is exclusionary of MDS-f. 8 Importantly, MDS-f does not apply to fibrotic MDS in the setting of low blast count. Given its adverse effect on prognosis that seems to extend to lower blast cases, reticulin staining and fibrosis grading should still be performed even on MDS cases with low blasts.…”
Section: Morphologic Classifiersmentioning
confidence: 99%